Hydrogen storage in porous polymer derived SiliconOxycarbide ceramics: Outcomes and perspectives. Issue 2 (15th January 2021) - Chauhan, P.K.; Parameshwaran, R.; Kannan, P.; Madhavaram, R.; Sujith, R.
Abstract: The present study explores the possibility of adopting thermally stable porous silicon oxycarbide (Si-O-C) ceramics as a suitable material for hydrogen storage. Experimental studies of hydrogen storage in these ceramics were conducted using Sievert's apparatus. A maximum specific surface area (SSA) of 158.1 m 2 /g with an average pore size of 14.5 nm was found for the ceramics. The ceramic showed gravimetric storage density (G.D) of 0.35 wt% at 2 bar and 100 K. Mesopore size, 2–5 nm was found critical for hydrogen adsorption in these ceramics. Hence, hydrofluoric acid etching was carried out to increase their count. Etching led to the removal of the SiO2 phase from the ceramic, thereby creating micro and mesoporosity and resulting in SSA of 451.6 m 2 /g with an average pore diameter of 4.36 nm. Further, the etched sample showed G.D of 1.19 wt% at 2 bar and 100 K, an increase of 240% over the un-etched sample. Additionally, the interaction potential of hydrogen with Si-O-C was calculated using the Clausius equation and was found to be dependent on the pore size in existing in the ceramic.